2005
DOI: 10.1111/j.1463-6409.2005.00208.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic relationships of corytophanid lizards (Iguania, Squamata, Reptilia) based on partitioned and total evidence analyses of sperm morphology, gross morphology, and DNA data

Abstract: Phylogenetic relationships of corytophanid lizards (Iguania, Squamata, Reptilia) based on partitioned and total evidence analyses of sperm morphology, gross morphology, and DNA data. -Zoologica Scripta , 34 , 605-625. We conducted partitioned and combined Bayesian and parsimony phylogenetic analyses of corytophanid lizards (Iguania) using mtDNA, gross morphology, and sperm ultrastructure data sets. Bayesian and parsimony hypotheses showed little disagreement. The combined analysis, but not any of the partition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
27
1
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 53 publications
(96 reference statements)
6
27
1
2
Order By: Relevance
“…However, the nuclear lacuna does not penetrate the entire nucleus and thus may have been missed in previous studies. The midpiece region is relatively short with the fibrous sheath beginning at mitochondria tier two which is consistent among phrynosomatids 7 but differs among other Iguania taxa 5 , 33 , 35 …”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…However, the nuclear lacuna does not penetrate the entire nucleus and thus may have been missed in previous studies. The midpiece region is relatively short with the fibrous sheath beginning at mitochondria tier two which is consistent among phrynosomatids 7 but differs among other Iguania taxa 5 , 33 , 35 …”
Section: Discussionsupporting
confidence: 65%
“…The acrosome is laterally compressed which resembles that of other taxa within Iguania 1 , 5 , 33 , 34 . A single perforatorium, a suggested synapomorphy for the squamata 4 , 34 extends into the acrosomal medulla.…”
Section: Discussionmentioning
confidence: 73%
“…Jamieson (1995a,b) considered the broad nuclear fossa of B. karrooicum as being pointed anteriorly, resembling those of sphenomorph skinks. Vieira et al (2005) also found a similar appearance of the nuclear fossa in corytophanid lizards.…”
Section: Zusammenfassungmentioning
confidence: 70%
“…In this way, we predict that discrete data will be much more conservative (less variable) than continuous ones. Another way to validate or reject our hypothesis is through the inclusion of other kinds of data sets, such as behavioural, ecological, molecular, morphological (gross morphology, sensu Vieira et al 2005), etc. Indeed, all groups discussed here are speculative entities that are based on indices (mainly decay index) that are indicators of ambiguity and evidential support, conferring it a heuristic value and pointing to more weak or ambiguously corroborated hypothesis (Grant and Kluge 2003).…”
Section: Choice Of the Best Hypothesismentioning
confidence: 99%
“…Accumulation of data, particularly recognizable variation in the developmental steps of spermiogenesis as outlined here for Scincella laterale may be phylogenetically significant. Mature sperm have been used recently for phylogenetic analysis Teixeira et al, 1999b;Vieira et al, 2004;Vieira et al, 2005) and differences that occur between lizard taxa during spermiogenesis can improve these databases by adding developmental and ontogenetic perspectives that supplement the present nontraditional data used for phylogenetic analysis. These data may ultimately help in our overall understanding of the phylogenetic relationships in Sauria and give us better perspective on the placement of lizard taxa within the order Squamata and the class Reptilia.…”
Section: Discussionmentioning
confidence: 99%